Thermal investigation on HSPM with new alloy sleeve - Zhang, Xiaochen; Li, Weili; Zhang, He; Gerada, C.; Gerada, David; Li, Jing (2017)
This paper presents a developed copper-iron alloy which made as the rotor sleeve in a high speed permanent magnetic machine (HSPMG), whist investigating its benefits in improve machine thermal performance. The features of the new alloy is experimental tested against the performance, which includes the conductivity, the permeability, and thermal conductivity, and the variation of loss distribution inside machine with sleeve conductivity and permeability are studied. A fluid-thermal coupled analysis model is proposed, by using which the fluid velocity and temperature distribution are obtained via numerical analyzing. The variations of machine operating temperature with new material are evaluated.